Physical and social cues shape nest-site preference and prey capture behavior in social spiders. (14th February 2020) - Najm, Gabriella M; Pe, Angelika; Pruitt, Jonathan N; Pinter-Wollman, Noa
Abstract: Animals often face conflicting demands when making movement decisions. To examine the decision process of social animals, we evaluated nest-site preferences of the social spider Stegodyphus dumicola . Colonies engage in collective web building, constructing 3D nests and 2D capture webs on trees and fences. We examined how individuals and groups decide where to construct a nest based on habitat structure and conspecific presence. Individuals had a strong preference for 3D substrates and conspecific presence. Groups were then provided with conflicting options of 3D substrates versus 2D substrates with a conspecific. Groups preferred the 3D structures without presettled conspecifics over a 2D substrate with conspecifics. When a group fragmented and individuals settled on both substrates, the minority group eventually joined the majority. Before rejoining, the collective prey capture behavior of divided groups improved with the size of the majority fragment. The costs of slow responses to prey for split groups and weak conspecific attraction may explain why dispersal is rare in these spiders. Abstract : Animals often face conflicting demands when choosing a nest site. Using social spiders, we determined that individuals use conspecific cueing and structural information in their selection process. When presented with conflicting social and structural information regarding nest-site quality, groups chose a preferred structure over another with a pre-established conspecific. These choices influenced collective behavior as groups that reached a consensus had higher prey capture success than groups that were split between nest sites.